Survival and causes of death among released brown hares (Lepus europaeus Pallas, 1778) in Central Poland - Misiorowska, Magdalena (Springer-Verlag, 2012)
We describe the results of our research on population dynamics among brown hares reared in enclosures and then released into suitable natural habitat. Radio-tracking was used to follow the fate of 60 released brown hares over a 4-year period, extending between November 2005 and November 2009. The survival rate among these animals after 12 months was estimated to be 37 %, with 22 tagged individuals surviving beyond 1 year post-release. The highest (40 %) level of mortality characterised the first month after release, while a second period of enhanced mortality coincided with the breeding season (altogether accounting for a 20 % mortality rate). There was no significant relationship between body mass and mortality rate in the first month following release. A natural cause of death was predation by mammals, which accounted for some 31 % of all losses. Remaining causes were poaching (13 %), hits by vehicles (7 %) and unidentified causes (9 %). However, in at least 40 % of cases, it was not possible to determine the date when a released animal died, to say nothing of the cause of death.